The Synergistic Effect of Tacrolimus (FK506) or Everolimus and Azoles Against Scedosporium and Lomentospora Species In Vivo and In Vitro - Wang, Zikuo; Liu, Mei; Liu, Luyao; Li, Linyun; Tan, Lihua; Sun, Yi (Frontiers in Cellular and Infection Microbiology, 2022)
Scedosporium and Lomentospora infections in humans are generally chronic and stubborn. The use of azoles alone cannot usually inhibit the growth of fungi. To further explore the combined effect of multiple drugs and potential mechanisms, we tested the antifungal effects of tacrolimus and everolimus in combination with azoles in vitro and in vivo on 15 clinical strains of Scedosporium/Lomentospora species and detected the level of Rhodamine 6G, ROS oxidation, and apoptosis. The results showed that the synergistic rates of tacrolimus with posaconazole, itraconazole, and voriconazole were 47%, 60%, and 73%, respectively. The synergistic rate of everolimus with posaconazole was 47%, and that with itraconazole and voriconazole was 53%. The synergistic effects might correspond to the elevated ROS oxidation (tacrolimus + itraconazole group compared with itraconazole group, (P < 0.05)), early apoptosis (itraconazole (P < 0.05) and voriconazole (P < 0.05) combined with everolimus), and late apoptosis (tacrolimus + itraconazole group compared with itraconazole group, (P < 0.01); tacrolimus + posaconazole group compared with posaconazole group, (P < 0.05)), but not to efflux pump. Our in vitro results suggested that a combination of tacrolimus or everolimus and azoles have a synergistic effect against Scedosporium/Lomentospora. The synergistic mechanisms might be triggering excessive ROS oxidation and apoptosis. In vivo, the survival rate of larvae was significantly improved by tacrolimus alone, everolimus alone, azoles alone, and tacrolimus and everolimus combined with azoles separately (P < 0.05 for tacrolimus group; P < 0.01 for everolimus group and itraconazole group; P = 0.0001 for tacrolimus and posaconazole group; P < 0.0001 for other groups except everolimus and itraconazole group, everolimus and posaconazole group, and tacrolimus and itraconazole group).